2016
DOI: 10.3892/etm.2016.3737
|View full text |Cite
|
Sign up to set email alerts
|

Gan-Dan-Liang-Yi-Tang alleviates p-chlorophenylalanine-induced insomnia through modification of the serotonergic and immune system

Abstract: Gan-Dan-Liang-Yi-Tang (GDLYT) is a Traditional Chinese Medicine that has been historically used for the treatment of insomnia. However, investigations into its pharmacological ingredients and the mechanism underlying its sedative and hypnotic effects remain limited. The present study reported the detailed mechanisms underlying the sedative and hypnotic effects of GDLYT. Kunming mice were administered GDLYT at various sub-hypnotic doses, which underwent sodium pentobarbital treatment test, pentetrazole induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…The I-κ/NF-κB signaling pathway is associated with sleep regulation and the immune system and hippocampus play a central role in insomnia ( 60 ). A previous study demonstrated that plasma levels of IL-6 and TNF-α in PCPA-induced insomnia rats were significantly higher compared with the control group ( 25 ). In the current study, the results demonstrated that the serum content of IL-1β, IL-6 and TNF-α and mRNA expression of IL-6, TNF-α and NF-κB in neural tissues in the PCPA+D-gal group were higher compared with control rats.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The I-κ/NF-κB signaling pathway is associated with sleep regulation and the immune system and hippocampus play a central role in insomnia ( 60 ). A previous study demonstrated that plasma levels of IL-6 and TNF-α in PCPA-induced insomnia rats were significantly higher compared with the control group ( 25 ). In the current study, the results demonstrated that the serum content of IL-1β, IL-6 and TNF-α and mRNA expression of IL-6, TNF-α and NF-κB in neural tissues in the PCPA+D-gal group were higher compared with control rats.…”
Section: Discussionmentioning
confidence: 91%
“…The ageing model induced by D-gal has been widely used (21,22) and has been evaluated in behavioral, biochemical and neurochemical aspects (23). The modeling methods of animal models of insomnia mainly include chemical reagent stimulation using intraperitoneal injection of para-chlorophenylalanine (PCPA) (24), the horizontal platform environmental deprivation method (25), the stress stimulation sleep deprivation method (26), the gentle stimulation deprivation method and the forced exercise deprivation method (27). Rat and mouse models can be used; however, rat models are optimal due to model stability in the establishment of the ageing model induced by D-gal (28).…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the activity and characteristics of LD extract on alleviating insomnia, the PCPAinduced insomnia test and spontaneous exploration activities were performed. The PCPA-induced insomnia rat model is the most commonly used classic model to study the mechanism of insomnia, which can deplete the 5-HT content in the brain, and is accompanied by dysfunction of the HPA axis (Hu et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The PCPA-induced insomnia rat model is the most commonly used classic model to study the mechanism of insomnia, which can deplete the 5-HT content in the brain, and is accompanied by dysfunction of the HPA axis (Hu et al. 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sixty male mice were randomly and evenly distributed into ve groups: blank control, PCPA (model, BH, DH and BDT groups. Except for mice in the control group, mice in the rest of the groups were intraperitoneally administrated with PCPA (300 mg/kg) once a day at 8:00 and 9: 00 a.m. for the rst and second day, respectively, to induce insomnia (Hu et al, 2016). Herbal medicines (BH, DH or BDT) were orally administrated 2 days after PCPA injection.…”
Section: Pentobarbital-induced Sleep Testmentioning
confidence: 99%